2022
DOI: 10.1177/00031348221096589
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization and Outcomes of Colorectal Malignancy in Patients ≤40 Years of Age: A Single-Center Experience

Abstract: Background Implementation of screening modalities has led to a decreased incidence of colorectal malignancies. Unfortunately, overall incidence has remained unchanged as cases have increased in patients below the suggested screening age. Therefore, we evaluated characteristics and oncological outcomes of malignancies in patients ≤40 years of age. Methods Single-center retrospective analysis of prospectively collected data of malignancies in patients ≤40 years evaluated in our institution between 2010 and 2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…They also showed a higher ratio of dMMR, along with a greater incidence of perineural and vascular invasion. These observations were similar to the ndings of Gabriel et al [21][22][23], who reported that EOCRC becomes more aggressive as the tumor stage advances. These changes might be attributed to advanced tumor staging that commonly occurs in EOCRC patients.…”
Section: Discussionsupporting
confidence: 91%
“…They also showed a higher ratio of dMMR, along with a greater incidence of perineural and vascular invasion. These observations were similar to the ndings of Gabriel et al [21][22][23], who reported that EOCRC becomes more aggressive as the tumor stage advances. These changes might be attributed to advanced tumor staging that commonly occurs in EOCRC patients.…”
Section: Discussionsupporting
confidence: 91%
“…Of the 12 859 unique articles retrieved, 699 full texts were reviewed, and 81 studies were included (Figure 1 and Table). There were 76 cross-sectional studies, 4 case-control studies, and 1 cohort study .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 12 859 unique articles retrieved, 699 full texts were reviewed, and 81 studies were included (Figure 1 and Table). There were 76 cross-sectional studies, 4 case-control studies, and 1 cohort study . Studies were performed in Africa (5 studies), Asia or the Middle East (26 studies), Europe (19 studies), North America (23 studies), South America (5 studies), and Oceania (2 studies) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations